Case study on the effects of fit and material of sports gloves on hand performance. (February 2019) - Yu, A.; Yick, K.L.; Ng, S.P.; Yip, J.
Abstract: Active and sports fashion in the high-end market focuses on fit, superior comfort and functional performance for various end-uses. However, the engineering design of sports gloves in relation to hand anthropometry measurements remains unclear. In this study, two types of ready-to-wear sport gloves, namely, war-gaming glove and hiking glove were purchased from the market. The glove dimensions, fabrication properties and the effect of glove fit on hand and finger dexterity were investigated. Thirty female individuals (20–29 years old) participated a series of hand performance tests and subjective perception rating assessments towards the gloves. Results indicated that the active range of motion of fingers, finger tactile sensitivity, gripping strength and ability to handle pegs and marbles decreased with the use of gloves compared with bare hands. The perceptions of comfort and ease of hand motions decreased with the increased of wear time. The glove fit in terms of finger length dimensions was significantly correlated with hand grip force. The glove fit in hand, wrist and finger circumference dimensions had significant impact on the ability to handle small objects. It is suggested that hand length, hand circumference, finger circumference and the ratio of finger length to palm length should be considered in the design and development of gloves to improve hand performance and comfort. Highlights: The effects of sports gloves and bare hands on hand performance are compared. Gripping force and ability to handle small objects are sensitive to glove fit. Glove fit with respect to hand and finger circumferences is correlated with hand dexterity and comfort.